2007
DOI: 10.1149/1.2458622
|View full text |Cite
|
Sign up to set email alerts
|

Structural Properties and Electrical Characteristics of Praseodymium Oxide Gate Dielectrics

Abstract: Structural properties and electrical characteristics of praseodymium oxide gate dielectrics grown on Si substrate by reactive rf sputtering were investigated. The structure, composition, and interfacial characteristics of these dielectrics were examined using X-ray diffraction and X-ray photoelectron spectroscopy. It is found that Pr 2 O 3 gate dielectric with TaN metal gate annealed at 700°C exhibits a higher capacitance value ͑ϳ450 pF, EOT = 2.41 nm͒ and lower flatband voltage ͑ϳ−0.5 V͒ in C-V curves, and sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 16 publications
2
17
0
Order By: Relevance
“…3. The spectra are in good agreement with those shown in [19] and [21]. The reference peak located at 933.9 eV for 3d and 928.8 eV for 3d is assigned to praseodymium in praseodymium oxide, respectively.…”
Section: A Physical Propertiessupporting
confidence: 86%
See 2 more Smart Citations
“…3. The spectra are in good agreement with those shown in [19] and [21]. The reference peak located at 933.9 eV for 3d and 928.8 eV for 3d is assigned to praseodymium in praseodymium oxide, respectively.…”
Section: A Physical Propertiessupporting
confidence: 86%
“…The intermediate energy state (531.8 eV) is attributed to interfacial O atoms in nonstoichiometric silicate (PrSi O ). The high energy state (533 eV) is attributed to O in SiO [19]. The feature at 531.8 eV is distinctly different from both O in SiO (high energy feature at 533 eV) and O in Pr O (low-energy feature at 530.7 eV).…”
Section: A Physical Propertiesmentioning
confidence: 92%
See 1 more Smart Citation
“…However, it is a difficult technological challenge to develop the enhancement of TFTs performance for both pixel and display circuits. Recently, it has been reported that LaAlO 3 and HfO 2 gate dielectrics [1,2] into LTPS TFTs exhibited excellent device performance due to their thin equivalent oxide thickness and high gate capacitance density. Furthermore, rare-earth-metal oxide films including La 2 O 3 and Pr 2 O 3 [3] have been studied to be suitable as gate oxides because of their high dielectric constant, large bandgap, and good thermodynamic stability in contact with poly-Si or Si.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Recently, we showed that thin praseodymium oxides are promising candidates for highly scaled gate insulators, displaying a lower interfacial density of state and smaller stress-induced leakage current. 11 In addition, it has been reported 12 that an amorphous PrTi x O y deposited on the Si by E-beam evaporation exhibited excellent electrical and physical properties. In this paper, we explore a high-k PrTi x O y nanocrystal film as the chargetrapping layer deposited on the tunneling oxide of memory devices using reactive radio frequency ͑rf͒ sputtering.…”
mentioning
confidence: 99%